Development of patient-specific, long-lasting bioabsorbable sinus implants in patients with chronic frontal sinusitis (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: The treatment of chronic frontal sinusitis is often problematic due to the anatomically narrow drainage into the nasal cavity. In addition to conservative methods, many surgical procedures have been analyzed, with and without the use of individual created placeholders, but without long-term therapeutic success. One of main novel and innovative placeholders of the last years is the Propel®mini, especially created for frontal sinus stenting. But fast material degradation and drug-eluting only up to 2 weeks after implantation and the predefined stent size was the motivation to look for a new bioabsorbable, drug-eluting sinus stent with anatomically perfect fitting through live 3D-printing and manufacturing during operations.Materials and Methods: The individual anatomical structures of the frontal sinus and its way of drainage are determined by segmentation of cone beam computed tomography (CBCT) imaging of 20 frontal sinuses. Different partners using varying additive manufacturing processes will develop individualised biodegradable drug implants. The additive manufacturing processes could be Fused Deposition Modeling, Digital Light Processing, Two-Photon-Polymerisation and Micro Injection Molding. This implants will be 3D printed directly in the operating room after automatic segmentation of individual anatomies of the frontal sinus. And then the individualised implants will be inserted into the patients frontal sinus.Results/Discussion: Due to the large individual anatomical variability of the frontal sinus and its way of drainage into the nasal cavity one new innovation is developing a 3D printed, patient individualised, biodegradable drug implant that fits exactly into the recess of the frontal sinus an its peripheral structures. This implant keeps the drug in place for months to get a much more dwell time and keep the drug delivery time extended.